Canadian Society of Transplantation White Paper: Ethical and Legal Considerations for Alcohol and Cannabis Use in Solid Organ Listing and Allocation. Issue 9 (19th August 2021) - Greenberg, Rebecca; Goldberg, Aviva; Anthony, Samantha; Buchman, Daniel Z.; Delaney, Sean; Gruben, Vanessa; Holdsworth, Sandra; Le Foll, Bernard; Leung, Marianna; Lien, Dale; Lynch, Marie-Josee; Selzner, Nazia; et al.
Abstract : Alcohol and cannabis use as a contraindication to organ transplantation is a controversial issue. Until recently, patients in Canada with alcohol-associated liver disease were required to demonstrate abstinence for 6 mo to receive a liver transplant. There is no equivalent rule that is applied consistently for cannabis use. There is some evidence that alcohol and cannabis use disorder pretransplant could be associated with worse outcomes posttransplantation. However, early liver transplantation for patients with alcohol-associated liver disease in France and in the United States has led to challenges of the 6-mo abstinence rule in Canada in the media. It has also resulted in several legal challenges arguing that the rule violates human rights laws regarding discrimination in the provision of medical services and that the rule is also unconstitutional (this challenge is still before the court). Recent legalization of cannabis use for adults in Canada has led to questions about the appropriateness of limiting transplant access based on cannabis use. The ethics committee of the Canadian Society of Transplantation was asked to provide an ethical analysis of cannabis and alcohol abstinence policies. Our conclusions were as follows: neither cannabis use nor the 6-mo abstinence rule for alcohol use should be an absolute contraindication to transplantation, and transplant could be offered to selected patients, further research should be conducted to ensure evidence-based policies; and the transplant community has a duty not to perpetuate stigma associated with alcohol and cannabis use disorders. Abstract :